Treatment of radiation-induced brachial plexopathy with omentoplasty - de Oliveira, Adilson José Manuel (Autops Case Rep, 2020)
Radiation-induced brachial plexus neuropathy (RIBPN) is a rare and delayed non-traumatic injury to the brachial plexus, which occurs following radiation therapy to the chest wall, neck, and/or axilla in previously treated patients with cancer. The incidence of RIBPN is more common in patients treated for carcinoma of the breast and Hodgkin lymphoma. With the improvement in radiation techniques, the incidence of injury to the brachial plexus following radiotherapy has dramatically reduced. The currently reported incidence is 1.2% in women irradiated for breast cancer. The progression of symptoms is gradual in about two-thirds of cases; the patients may initially present with paresthesia followed by pain, and later progress to motor weakness in the affected limb. We present the case of a 68-year-old female patient with breast cancer submitted to surgery, chemotherapy, and radiotherapy in the year 2000. Eighteen years later, she developed symptoms and signs compatible with RIBPN and was successfully submitted to omentoplasty for pain control. Omentoplasty is an alternative treatment for RIBPN refractory to conservative treatment, which seems to be effective in improving neuropathic pain. However, postoperative worsening of the motor strength is a real possibility, and all candidates for this type of surgery must be informed about the risk of this complication.